Spatial-Based Management of Van den Bosch Fortress to Revitalize Historical Assets and Develop Unique Cultural Tourism - Sugiarti, Rara; Warto, Warto; Supariadi, Supariadi (E-Journal of Tourism; Volume 7 Number 1 (March 2020)DO - 10.24922/eot.v7i1.58834, 2020)
Van den Bosch fortress is located in Ngawi East Java Indonesia. The fortress’ unique location in the riverbanks of two main rivers of Java island, i.e. Bengawan Solo river and Madiun river, boosts its potentilas as a cultural tourist attraction. The meeting point between these two big rivers has given the fortress opportunities to develop unique tourism package. This study examined the potentials of the fortress, problems for developing the fortress, and the interconnection of spatial distribution of the fortress by employing geographic information system (GIS) to develop spatial-based management of the fortress as an intergrated cultural tourism site. Spatial-based management of the historical resource is aimed at combining and enhancing the urban elements including town square, traditional market, fortress, and rivers as well as some supporting facilities; and it is expected to be able to make Van den Bosch fortress as the center of the attractions. All of the elements of the urban area need to be spatially planned and managed in order to perform a unique tourist attraction in the most enticing historical destination of the region. Keywords: cultural tourism, fortress, historical asset, spatial-based management.